Metaphor or Method. Jennifer Mensch’s Organicist Kant Interpretation in Context - Zöller, Günter (Con-Textos Kantianos. International Journal of Philosophy, 2015)
In her recent study, Kant’s Organicism.Epigenesis and the Development of Critical Philosophy (Chicago: Chicago University Press, 2013), Jennifer Mensch employs the technical term "organicism" to designate both Kant’s thinking about organisms and his thinking about other matters–chiefly among those transcendental cognition –in terms of his thinking about organisms. The article places Mensch’s organicist reading of Kant into the wider context of recent and current work on Kant as a natural historian (Naturforscher) and its repercussion for understanding the critical core of Kant’s philosophy. To that end, the article addresses the methodological function of conceptual metaphors in general and of biological metaphors in particular in Kant. The article proceeds in three steps, first focusing on an alleged anthropological turn in recent work on Kant, then addressing the distinction between schematism and symbolism in Kant’s critical epistemology and concluding with a consideration of the possibilities and limitations inherent in an organicist reading of Kant.